From Waste to Resource - Shifting Paradigms for Smarter Wastewater Interventions in Latin America and the Caribbean : Background Paper II. Showcasing the River Basin Planning Process through a Concrete Example - The Río Bogotá Cleanup Project - World Bank (World Bank, Washington, DC, 2020)
This background paper is part of the supporting material for the report “From Waste to Resource: Shifting Paradigms for Smarter Wastewater Interventions in Latin America and the Caribbean,” a product of the “Wastewater: from waste to resource,” an initiative of the World Bank Water Global Practice.